Índice de qualidade de efluente com ponderação de variáveis por método objetivo. - Araújo, Camylla Rachelle Aguiar (2023)
The sustainable management of water resources requires efficient control of the quality of effluents released into water bodies. This work aimed to propose an Effluent Quality Index (EQI) and the Effluent Quality Level (EQL) using entropy for objective weighting of the variables. The EQI and EQL are valuable tools for evaluating treatment technologies and supporting improvement actions. For this, seven parameters were selected, based on previous studies and Brazilian environmental legislation: Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), Ammonia Nitrogen (AN), Total Nitrogen (N), Total Phosphorus (P) and Thermotolerant Coliforms (TC). The study consisted of normalizing data from 13 sewage treatment technologies in order to allow adequate comparisons between different situations. Then, the entropy of variables in the raw and treated effluents was calculated to determine the weights. The final model aggregates the weighted sub-indices, generating an EQI between 0-100 and an EQL between 1-5 that are classified into five categories. For the indices, the quality of compliance with launch legislation was assessed according to the following service ranges: excellent (EQI 91-100; EQL 5), good (EQI 71-90; EQL 4), satisfactory (EQI 50- 70; EQL 3), unsatisfactory (EQI 25- 49; EQL2) and very bad (EQI 1-24; EQL 1). For validation, we carried out the application with real data from treatment plants using seven models out of the thirty-four that were proposed. The results improved the efficiency of the approach in representing effluent quality in a comprehensive and robust way. The entropy method is satisfactory for objective weighting taking into account data variability. EQI and EQL propose to support decision- making and management of effluent treatment, assisting in the selection of specific technologies and the identification of critical parameters.